Thomas Bedürftig und Roman Murawski, Philosophie der Mathematik, 3rd expanded and revised edition, xvii+465 pp, Walter de Gruyter, Berlin, 2015, ISBN: 978-3-11-033117-2/pbk; 978-3-11-033118-9/ebook. - DRĂGHICI, Virgil (Studia Universitatis Babeș-Bolyai Mathematica, 2015)
Any person, well acquainted with the history of mathematics, could grasp thefact that the development of mathematics is not a linear one. Indisputably, the mostnotable conceptual changing happened in the 19 century, a moment in which theanalysis of the real numbers, the set theory and the axiomatic approach impose anew paradigm, in which much of the old problems get a mathematical solution and inwhich new topics do generate new problems. This is the conceptual ground on which,in a very inspired and extremely exible mode, the mathematics and the philosophyencounter each other in an excellent book on the philosophy of mathematics.